First‐in‐man–proof of concept study with molidustat: a novel selective oral HIF‐prolyl hydroxylase inhibitor for the treatment of renal anaemia. (14th May 2018) - Böttcher, M.; Lentini, S.; Arens, E. R.; Kaiser, A.; van der Mey, D.; Thuss, U.; Kubitza, D.; Wensing, G.
Abstract : Aims: Insufficient erythropoietin (EPO) synthesis is a relevant cause of renal anaemia in patients with chronic kidney disease. Molidustat, a selective hypoxia‐inducible factor prolyl hydroxylase (HIF‐PH) inhibitor, increases endogenous EPO levels dose dependently in preclinical models. We examined the pharmacokinetics, safety, tolerability and effect on EPO levels of single oral doses of molidustat in healthy male volunteers. Methods: This was a single‐centre, randomized, single‐blind, placebo‐controlled, group‐comparison, dose‐escalation study. Molidustat was administered at doses of 5, 12.5, 25, 37.5 or 50 mg as a polyethylene glycol‐based solution. Results: In total, 45 volunteers received molidustat and 14 received placebo. Molidustat was absorbed rapidly, and the mean maximum plasma concentration and area under the concentration–time curve increased dose dependently. The mean terminal half‐life was 4.64–10.40 h. A significant increase in endogenous EPO was observed following single oral doses of molidustat of 12.5 mg and above. Geometric mean peak EPO levels were 14.8 IU l –1 (90% confidence interval 13.0, 16.9) for volunteers who received placebo and 39.8 IU l –1 (90% confidence interval: 29.4, 53.8) for those who received molidustat 50 mg. The time course of EPO levels resembled the normal diurnal variation in EPO. Maximum EPO levels were observed approximately 12 h postdose and returned to baseline after approximately 24–48 h. All doses of molidustat were well tolerated and there were no significant changes in vital signs or laboratory safety parameters. Conclusions: Oral administration of molidustat to healthy volunteers elicited a dose‐dependent increase in endogenous EPO. These results support the ongoing development of molidustat as a potential new treatment for patients with renal anaemia.